Cristina Moreno - Analysis of P-wave Changes for Prediction of Atrial Fibrillation Episodes - Moreno, Cristina (Jornada de Jóvenes Investigadores del I3A, 2022)
Analysis of P-wave Changes for Prediction of Atrial Fibrillation Episodes